A Theory of Mediators' Ethics: Foundations, Rationale and Application. By Omer Shapira. Issue 1 (24th September 2018) - Wilson, Barbara
Abstract : A Theory of Mediators' Ethics: Foundations, Rationale and Application By Omer Shapira Cambridge: Cambridge University Press Published: Hardback (2016) Paperback (2018) pp.: 498